Exploring learning content and knowledge transfer in baccalaureate nursing students using a hybrid mental health practice experience. (April 2017) - Booth, Richard G.; Scerbo, Christina Ko; Sinclair, Barbara; Hancock, Michele; Reid, David; Denomy, Eileen
Abstract: Background: Little research has been completed exploring knowledge development and transfer from and between simulated and clinical practice settings in nurse education. Objectives: This study sought to explore the content learned, and the knowledge transferred, in a hybrid mental health clinical course consisting of simulated and clinical setting experiences. Design: A qualitative, interpretive descriptive study design. Settings: Clinical practice consisted of six 10-hour shifts in a clinical setting combined with six two-hour simulations. Participants: 12 baccalaureate nursing students enrolled in a compressed time frame program at a large, urban, Canadian university participated. Methods: Document analysis and a focus group were used to draw thematic representations of content and knowledge transfer between clinical environments (i.e., simulated and clinical settings) using the constant comparative data analysis technique. Results: Four major themes arose: (a) professional nursing behaviors; (b) understanding of the mental health nursing role; (c) confidence gained in interview skills; and, (d) unexpected learning. Conclusions: Nurse educators should further explore the intermingling of simulation and clinical practice in terms of knowledge development and transfer with the goal of preparing students to function within the mental health nursing specialty. Highlights: the intermingling of simulation and practice can have a reciprocal learning and knowledge transfer benefit to the students students gained different elements of knowledge, experiences, and skills from simulation and agency-based practice settings observed poor practice in clinical environments conflicted with the best-practices modeled in simulation